Returning migrants in the republic of Macedonia: the Issue of Reintegration - Bornarova, Suzana (Two Homelands, 2011)
The Republic of Macedonia has been facing increased flows of returnees following their legal or illegal emigration abroad. This has led to the recognition of the issue of their social, economic and cultural reintegration into society. In order to respond to the needs of the returnees, the Government has developed a Programme for Reintegration of Returnees in Accordance with the Readmission Agreements. It is expected that this programme will add to the activities of the non-governmental organisations in assisting returnees and their families upon their voluntary or forced return in a more organised and systemic way.